Colloidal Quantum Dot Infrared Lasers Featuring Sub‐Single‐Exciton Threshold and Very High Gain. Issue 1 (21st November 2022) - Taghipour, Nima; Dalmases, Mariona; Whitworth, Guy L.; Dosil, Miguel; Othonos, Andreas; Christodoulou, Sotirios; Liga, Shanti Maria; Konstantatos, Gerasimos
Abstract: The use of colloidal quantum dots (CQDs) as a gain medium in infrared laser devices has been underpinned by the need for high pumping intensities, very short gain lifetimes, and low gain coefficients. Here, PbS/PbSSe core/alloyed‐shell CQDs are employed as an infrared gain medium that results in highly suppressed Auger recombination with a lifetime of 485 ps, lowering the amplified spontaneous emission (ASE) threshold down to 300 µJ cm −2, and showing a record high net modal gain coefficient of 2180 cm −1 . By doping these engineered core/shell CQDs up to nearly filling the first excited state, a significant reduction of optical gain threshold is demonstrated, measured by transient absorption, to an average‐exciton population‐per‐dot 〈 N th 〉g of 0.45 due to bleaching of the ground state absorption. This in turn have led to a fivefold reduction in ASE threshold at 〈 N th 〉ASE  = 0.70 excitons‐per‐dot, associated with a gain lifetime of 280 ps. Finally, these heterostructured QDs are used to achieve near‐infrared lasing at 1670 nm at a pump fluences corresponding to sub‐single‐exciton‐per‐dot threshold (〈 N th 〉Las  = 0.87). This work brings infrared CQD lasing thresholds on par to their visible counterparts, and paves the way toward solution‐processed infrared laser diodes. Abstract : Heavily doped PbS/PbSSe core/alloyed‐shell colloidal quantum dots (CQDs) lead to short‐wave infrared lasers with sub‐single‐exciton pump threshold. These CQDs exhibit strong suppression of Auger recombination thanks to their compositional grading at the core/shell interface. Besides, they offer record high modal gain coefficient as well as long optical gain lifetime.